THE INFLUENCE OF COMPETENCE ON PERFORMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE ON MEDICAL EMPLOYEES IN AMERICA PUBLIC SERVICE DEPARTMENT - Richard Frimpong Oppong; Weihuan Zhau (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
In this study, the population was employees of Medical Employees In America Public Service Department, namely as many as 43 people. Because the target population is less than 100, the sampling technique used is the census method, where the entire population of 43 people will be used as the research sample. With the results of the first hypothesis being accepted, it means that the Competency variable (X) has a positive and significant effect on Motivation (Z). the second hypothesis is rejected, meaning that Competence (X) has no positive and significant effect on Employee Performance (Y). the third hypothesis is accepted, meaning that motivation (Z) has a positive and significant effect on employee performance (Y).